Patterns of use, perceived benefits and reported effects of access to navigation support systems: an inter‐European field operational test. Issue 8 (1st October 2015) - Karlsson, I.C. MariAnne; Skoglund, Tor; Wallgren, Pontus; Alonso, María; Guidotti, Leandro; Martin, Oscar; May, Andrew
Abstract : The study presents findings regarding drivers' patterns of use, attitude towards, and reported effects of access to mature nomadic navigation support systems. Three different systems were tested by 582 drivers in four‐field operational tests for a period of six months. A majority of the participants used the support system for trips where the route/destination was unfamiliar but there were also other use scenarios. The main benefits entailed convenience and comfort. Reported effects involved increased possibilities to choose the route according to preferences; a decrease in the time it took to reach destinations and in the distance covered to reach the destination. One in four reported a decrease in fuel consumption attributed an increased compliance with speed limits and/or that driving around and searching for the correct route to reach the desired destination could be avoided. A majority reported 'no change' regarding the number of journeys made by car. Reported effects (whether increases or decreases) were however smaller than expected before the trial.